In-silico Analysis Of Maricaffeoylide From Avicennia Marina Using Molecular Docking With Tumor Necrosis Factor Receptor - Lulu Setiyabudi; Nila Fadila Ulya; Septiana Indratmoko; Mika Tri Kumala Swandari (Biomedical Journal of Indonesia, 2022)
Introduction. Bioactive metabolites was isolated from Avicennia marina fruit belongs to a new caffeoyl derivative, maricaffeoylide. It was a class of phenolic compounds such as caffeic acid which had potential as anticancer, anti-inflammatory, and antioxidant activity. One of proinflammatory cytokine that play a role in regulating immune cells against cancer is TNF-α. In-silico analysis is often used to molecular docking. It was carried out to determine the interaction molecule between bioactive compound and receptor. The purpose of this study is to analysed of interaction maricaffeoylide and TNF-α receptor using molecular docking. In this study, molecular docking will be carried out to determine the interaction and affinity of the bond energy. Methods. The method used in this research is experimental which is carried out in silico using molecular docking. Maricaffeoylide was prepared by using Marvin Sketch and TNF-α receptor was downloaded from pdb. Molecular docking was carried out ligand and receptor preparation, validation, molecular tethering using Pyrx-Autodock Vina, and visualization by BIOVIA. Result. The result of the conformation of the maricaffeoylide has an energy of 69.77 kcal/mol. The gridbox is adjusted at center coordinates x = 14.85; y = -6.50; and z = -6.70 and at dimensions x = 31, y = 35, and z = 63 Ǻ. The Lipinski’s rule for drug-likeness was confirmed. Conclusion. Molecular docking of maricaffeoylide against TNF-α receptors was successfully performed with a docking score of -6.1 kcal/mol involving the interaction van der Waals, hydrogen, alkyl, and carbon hydrogen.